2006
DOI: 10.1002/bies.20412
|View full text |Cite
|
Sign up to set email alerts
|

From genes to aggressive behavior: the role of serotonergic system

Abstract: Recent investigations in neurogenomics have opened up new lines of research into a crucial genetic problem-the pathway from genes to behavior. This paper concentrates on the involvement of protein elements in the brain neurotransmitter serotonin (5-HT) system in the genetic control of aggressive behavior. Specifically, it describes: (1) the effect of the knockout of MAO A, the principal enzyme in 5-HT degradation, (2) the association of intermale aggression with the polymorphism in the Tph2 gene encoding the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
106
0
6

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(120 citation statements)
references
References 75 publications
8
106
0
6
Order By: Relevance
“…The heightened aggressive behavior of 5-HT1BÀ/À mice is one of many findings in both animals and humans that support a role for the 5-HT system in regulating aggressive behavior (Hen, 1996;Oquendo and Mann, 2000;Popova, 2006). Our finding of increased 5-HIAA in the hippocampus of Egr3À/À mice (Table 1) indicates an abnormality in 5-HT turnover, and suggests a possible mechanism through which Egr3 may be affecting aggressive and impulsive behavior.…”
Section: Aggression In Egr3à/à Micesupporting
confidence: 53%
See 1 more Smart Citation
“…The heightened aggressive behavior of 5-HT1BÀ/À mice is one of many findings in both animals and humans that support a role for the 5-HT system in regulating aggressive behavior (Hen, 1996;Oquendo and Mann, 2000;Popova, 2006). Our finding of increased 5-HIAA in the hippocampus of Egr3À/À mice (Table 1) indicates an abnormality in 5-HT turnover, and suggests a possible mechanism through which Egr3 may be affecting aggressive and impulsive behavior.…”
Section: Aggression In Egr3à/à Micesupporting
confidence: 53%
“…Altered function of the 5-HT and DA systems has been associated with increased aggression in mice and humans (Hen, 1996;Miczek et al, 2002;Gordon and Hen, 2004;Popova, 2006). In animal models, manipulations of serotonin result in changes in aggression, and inactivation of 5HT-1B receptors in mice results in increased impulsive aggression (Saudou et al, 1994;Bouwknecht et al, 2001).…”
Section: Regional Changes In Serotonergic and Dopaminergic Systemsmentioning
confidence: 99%
“…For example, the penetrance of the fused phenotype is altered in the progeny of mouse parents treated with hydrocortisone (Belyaev et al 1983). In silver foxes selected for tame behavior, hormonal effects in the serotonin system that controls aggression seem to be involved in the heritable activation of the star gene that leads to white spotting (Belyaev et al 1981a,b;Trut et al 2004;Popova 2006). The best investigated case of hormonally-mediated effects on epigenetic marks is that of the transgenerational effect of the estrogenic androgen disruptors vinclozolin and methoxychlor on testes development in male rats (Anway et al 2005(Anway et al , 2006aChang et al 2006;Crews et al 2007).…”
Section: Cases Included In the Tablementioning
confidence: 99%
“…These reversible changes could not be explained as an effect of inbreeding either, because the coefficient of inbreeding was only 0.03 (Trut et al 2004). A probable explanation is that the stress of domestication and selection for tameness targeted genes with large effects in the neuro-hormonal system (Trut et al 2004;Popova 2006) and may have heritably reactivated some of them (Belyaev 1981a,b). This epigenetic interpretation, in terms of new epimutations rather than new mutations, explains the high rate of appearance and disappearance of some phenotypes, and support for this comes from the fact that at least two of the genes (Agouti and C-kit) that seem to be involved in the changes are known to have heritable epigenetic variants in mice (Trut et al 2004).…”
Section: Evolution Through Selection Ofmentioning
confidence: 99%
“…Several conserved neuromodulators have been shown to play a role in fly aggression [5][6][7] . For example, serotonin plays a critical role in the modulation of aggression across a broad range of species but the effect is different in vertebrates and invertebrates 13,14 . In addition, fly-specific pheromonal cues have been identified that affect aggression in Drosophila [10][11][12] .…”
mentioning
confidence: 99%